The role of phonological awareness and pinyin knowledge in Chinese character reading among Arabic-speaking learners (Philology, 2026)
With the growing enthusiasm for learning Chinese in Arabic-speaking countries, research on the learning patterns of Arabic-speaking learners of Chinese deserves greater attention. This study examines the role and pathway of phonological awareness and Pinyin knowledge in the Chinese character reading of Arabic-speaking learners at beginner and intermediate levels. The results show that Pinyin knowledge significantly predicts both reading accuracy and fluency at both proficiency levels, although its effect on reading fluency diminishes at the intermediate level. Auditory phonological awareness does not directly predict Chinese character reading, but exerts an indirect influence through the mediation of Pinyin knowledge. Furthermore, reading accuracy serves as a strong predictor of the development of reading fluency. Based on these findings, the study offers pedagogical suggestions for teaching Chinese characters to Arabic-speaking learners.
Keywords: phonological awareness; Pinyin knowledge; reading accuracy; reading fluency; Arabic-speaking learners